Assessment of genetic variability among Fusarium oxysporum f. sp. cumini isolates based on pathogenicity and RAPD markers - R.A. SHARMA; JAGDISH PRASAD, SANGEETA MEHTA, V.K. GAUR* (Indian Phytopathology, 2012)
Genetic variability among ten isolates of Fusarium oxysporum f. sp. cumini, the incitant of wilt of cumin was assessed by using pathogenicity and RAPD markers. Isolates varied in pathogenicity both in sterile and unsterile soil when tested on cumin var. RZ-19. The Bikaner isolate was highly virulent, followed by isolates from Tonk, Nagaur, Barmer, Jalore, Jaisalmer, Sikar, Jodhpur, Ajmer and Jhunjhunu. The wilt incidence (%) in sterile and unsterile soil varied from 23.31 to 95.00 and 18.46 to 80.00, respectively. Isolates were also differentiated in the RAPD banding pattern. The similarity value of RAPD profiles ranged from 0.21 (Sikar and Tonk) to 0.68 (Nagaur and Tonk) with an average of 0.45 Â± 0.1 among the isolates. The cluster analysis using un-weighted pair group method with arithmetic average distinguished Fusarium oxysporum isolates into different fingerprint groups.